High-throughput synthesis of bulk thermoelectric chalcogenides - Zhu, Haojun (Nanyang Technological University, 2024)
This study explores the high-throughput synthesis of p-type ternary chalcogenides bismuth antimony telluride Bi2-xSbxTe3 (BST), specifically targeting compositions of Bi0.4Sb1.6Te3, Bi0.5Sb1.4Te3 and Bi0.6Sb1.4Te3. Using the in-house developed 6S, a self-sintered scalable solid-state synthesis technique, we synthesised bulk BST thermoelectric materials with competitive thermoelectric performance. Comprehensive materials characterisations, including Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDX), X-Ray Diffraction (XRD) and electronic transport measurements were conducted to obtain the relationship between structural, compositional, and thermoelectric properties. Crucially, we benchmarked our material with existing literature, aiming to draw comparisons at the material property level. Our findings demonstrate the potential of high-throughput methodologies in accelerating the development and optimisation of novel thermoelectric materials.